1990
DOI: 10.1007/bf00046909
|View full text |Cite
|
Sign up to set email alerts
|

Julia sets for the gamma recursion in nonlinear psychophysics

Abstract: Julia sets for the map z ~ alz -ie)(1 -zXz + ie) are illustrated for some attractors of interest. This work extends previous analyses of the cubic complex polynomial and considers dynamics in regions which may be associated with the modelling of the results of overload in sengory inputs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1991
1991
1994
1994

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…The r recursion (Campbell & Gregson, 1990;Gregson, 1988Gregson, , 1989aGregson, , 1989bGregson & Britton, 1989;Price & Gregson, 1988) in two-variable form is…”
Section: Attractor Propertiesmentioning
confidence: 99%
“…The r recursion (Campbell & Gregson, 1990;Gregson, 1988Gregson, , 1989aGregson, , 1989bGregson & Britton, 1989;Price & Gregson, 1988) in two-variable form is…”
Section: Attractor Propertiesmentioning
confidence: 99%
“…It is found that this recursion exhibits very complicated dynamics (Campbell & Gregson, 1990; Price & Gregson, 1988) with interplay of the effects of a and e. As ( 7 ) is a nonlinear mapping from a onto Y, for a given Yo, values of a which correspond to stimulus levels 4 (input does not map directly onto Y) can induce single or multiple values of Y,, though obviously not both at once, and the evolution of Y becomes periodic, quasi-periodic or chaotic as a function of the two parameters a and e. If we generate, in time, a sequence of u values as stimulus inputs, which is almost continuous and monotone increasing, the corresponding sequence of Y( Re) values, which predict the observable outputs, will not necessarily exhibit the same monotonicity. The r trajectory can be written as two evolutions, cross-coupled in two real variables (Campbell & Gregson, 1990; Gregson, 1991) but this is not to be interpreted as a signal and a noise channel in parallel; the e variable's main role is to modify critically the shape of the psychometric function, and the points at which there are changes in the system dynamics from point output (single-valued Y,(Ke)) to limit cycling within r trajectory evolution, and on to chaos. Chaos is only associated with sensory overload, which does not appear usually in the present task context.…”
Section: Nonlinear Analysismentioning
confidence: 99%
“…Its properties within a stable region have been shown to reproduce a diversity of empirical phenomena which are of interest to experimental psychologists. Its behaviour in the neighbourhoods of its higher attractors has been explored more recently (Campbell & Gregson 1990). These regions are of potential interest because they may be interpreted as evidence of system dynamics where there is sensory overload and a predictable breakdown of normal functioning.…”
mentioning
confidence: 99%